Pre-Primary Education in South Sudan : Current Opportunities and Challenges - World Bank Group; UNICEF (World Bank, Washington, DC, 2019)
The objective of this report is to support evidence-based decision making for the pre-primary education system in South Sudan, and to identify critical bottlenecks and potential pathways for further engagement aimed at improving and rebuilding the subsector. To understand the current landscape of pre-primary education in South Sudan, this report draws on findings from three key sources: (i) review of early childhood education in contexts of fragility, conflict and violence; (ii) situation analysis of pre-primary education in South Sudan; and (iii) findings from the pre-primary Stakeholder Diagnostic Workshop held in Juba, South Sudan on February 11-14, 2019 facilitated by UNICEF and the World Bank. Findings from a review of all available policy documents and outcomes of the stakeholder diagnostic workshop are organized in this report by the five action areas specified in UNICEF’s pre-primary education diagnostic toolkit: (i) effective planning and use of resources; (ii) curriculum development and implementation; (iii) teachers and other personnel; (iv) families and communities; and (v) monitoring, regulation and quality assurance. The report ends with stakeholder recommendations for creating an enabling environment for pre-primary education in South Sudan.